Signs of trouble: semiotics, streetscapes, and the Republican struggle in the North of Ireland - Welch, Michael (Crime, media, culture, 2020)
Just as the political divisions in the North of Ireland are subject to ongoing critique, so too is its culture that maintains what scholars recognize as contested heritage. Ethno-political symbols, such as flags and murals, not only point to certain identities but also mark their territory. Whereas those emblems have been the subject of extensive research, political posters remain an overlooked source of rich iconography. This article fills that void by examining a collection of posters on display at the Irish Republican History Museum in West Belfast. The posters, in their original incarnation, emboldened the streetscapes of urban zones during ?the Troubles??a euphemism used to depict sectarian violence from the 1960s to the 1990s. In their afterlife, those posters have been preserved as material artefacts consumed by political tourists interested in gaining insight into the dissonance of heritage. Semiotics?the study of signs?provides a theoretical paradigm for this interpretation of the posters and their meaning. Moreover, Juri Lotman?s notion of the semiosphere (semiotic space) adds a deeper layer of analysis by directing critical attention to the role of the boundary where the performance of signs is most intense.